2020
DOI: 10.3390/ani10101786
|View full text |Cite
|
Sign up to set email alerts
|

Organic Dairy Cattle: Do European Union Regulations Promote Animal Welfare?

Abstract: Animal welfare is an emerging concept in EU law; with the advent of specific regulations intending to protect animals. The approach taken by European lawmakers is to provide “minimum standards” for conventional farming; argued by some as failing to adequately protect animals. In contrast, the EU organic farming regulations aim to “establish a sustainable management system for agriculture” and promote “high animal welfare standards”. The first aim of this review was to identify key areas where there are clear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 196 publications
(234 reference statements)
0
8
0
Order By: Relevance
“…Varying regulations and limits of permitted conventional manure complicate the comparisons within MS, making consumer education difficult. Antibiotics in Organic Farming can only be used if alternative treatments fail, they must be approved by a veterinarian, and no animal can receive more than three treatments per year (Duval et al, 2020), except for vaccinations, treatments against parasites and compulsory eradication schemes. If the animal's life cycle is less than one year, only one treatment is possible.…”
Section: Tablementioning
confidence: 99%
“…Varying regulations and limits of permitted conventional manure complicate the comparisons within MS, making consumer education difficult. Antibiotics in Organic Farming can only be used if alternative treatments fail, they must be approved by a veterinarian, and no animal can receive more than three treatments per year (Duval et al, 2020), except for vaccinations, treatments against parasites and compulsory eradication schemes. If the animal's life cycle is less than one year, only one treatment is possible.…”
Section: Tablementioning
confidence: 99%
“…Donkey milk is considered a healthy substitute for breast milk or an alternative to cow’s milk in children with cow’s milk allergy; it has antimicrobial properties and it must respect the same standards as organic cow’s milk [ 42 ]. European Union organic farming regulations aim to both offer high standards in animal welfare and to also promote sustainable management in agriculture; however, this can be vague in terms of actual application [ 43 ] and, in the case of this donkey farm, might have contributed to a high morbidity and mortality of the outbreak. Moreover, anthelmintic treatment is restricted in dairy production due to the elimination of different molecules in milk, which, in cattle, leads to higher parasite infection rates [ 44 ] and might do so as well in milk producing donkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Other scientific papers have shown that organic herd management system is associated with a reduction of the incidence of lameness [19,[29][30][31]. This is likely due to the access to pasture, which in ORG farms must be granted by law [4], that can prevent lameness in animals [32][33][34]. To support this, Silva et al [35] reported a low prevalence of lameness in cows that had access to pasture on both CONV and ORG farms.…”
Section: Welfare Assessmentmentioning
confidence: 99%